If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 8 + -4x = 0 Reorder the terms: 8 + 5x + -4x = 0 Combine like terms: 5x + -4x = 1x 8 + 1x = 0 Solving 8 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = 0 + -8 1x = 0 + -8 Combine like terms: 0 + -8 = -8 1x = -8 Divide each side by '1'. x = -8 Simplifying x = -8
| 6+2(z+3)=-4(2z+6) | | 2y-3+3(3y+4)=-3(y+1) | | 1=3-c | | 2m+6=-10 | | 10/10-10/1 | | 10t+t+t-t-t=10 | | (4(y-6))/3=-2y | | -4(-m-5)-7=-11 | | 0=4p-28 | | x+10=x+90 | | 1/2x+5=1/2x-3 | | 5(p-6)=8p-21 | | -(9m+10)+2= | | 8u-8u+u-1=5 | | 12+2n=5n | | 7-5(x+8)=43 | | 8c+2b= | | 4(k+6)=56 | | -5x=3x+6 | | 9p-5p-9-2p=10 | | 6a-16=2(a-6) | | 16=6ty | | 16=6tyv | | 3.045+3b=2.73b+2.4+0.7b | | 8n+22=3 | | -7/2=-6/5x-7/3 | | 5+6p=41 | | -12/k=-4 | | 1(2x-4)=2(4-6x) | | 13/20-1/6 | | 18+6m=5+(-4m) | | 3(x-3)=6x-6-3x |